Explicit iteration and unbounded solutions for fractional q-difference equations with boundary conditions on an infinite interval - Boutiara, Abdellatif (Springer, 2022)
In this work, a proposed system of fractional boundary value problems is investigated concerning its unbounded solutions' existence for a class of nonlinear fractional q-difference equations in the context of the Riemann-Liouville fractional q-derivative on an infinite interval. The system's solution is formulated with the help of Green's function. A compactness criterion is established in a special space. All the obtained results of uniqueness and existence are investigated with the help of fixed-point theorems. Some essential examples are illustrated to support our main outcomes.